Corrective Emotional Experience in Couple Therapy: An Integration between Imago Approach and Psychoanalytic Concepts in Light of Neuropsychological Studies. Issue 4 (2nd October 2021) - Noy-Sharav, Dorit
Abstract: The article examines the potential contribution of psychoanalytic concepts—such as manic defense and corrective emotional experience—to couple therapy, especially to Imago Relationships Therapy (IRT). Several vignettes demonstrate how the IRT dialogue, characterized by a horizontal and close setting, inspires a reexperiencing of painful memories, triggering their automatic defensive behavior patterns, and offers empathic, validating responses. Integrating relevant findings from neuroscience, it demonstrates how activating mirror neurons, reducing reactivity, stimulating oxytocin and the dopamine reward system via IRT afford the three necessary steps for unlocking the emotional brain, leading to a reconsolidation of healthier, more satisfying patterns of relationships.